If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 8 = 2(2x + -4) Reorder the terms: 8 + -4x = 2(2x + -4) Reorder the terms: 8 + -4x = 2(-4 + 2x) 8 + -4x = (-4 * 2 + 2x * 2) 8 + -4x = (-8 + 4x) Solving 8 + -4x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + -4x + -4x = -8 + 4x + -4x Combine like terms: -4x + -4x = -8x 8 + -8x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + -8x = -8 + 0 8 + -8x = -8 Add '-8' to each side of the equation. 8 + -8 + -8x = -8 + -8 Combine like terms: 8 + -8 = 0 0 + -8x = -8 + -8 -8x = -8 + -8 Combine like terms: -8 + -8 = -16 -8x = -16 Divide each side by '-8'. x = 2 Simplifying x = 2
| -27=-x+24 | | 12-(x+3)=74 | | 1/2x-7=11-1/2x | | C=3.50+1.25(16-1) | | -12x+24y-38-5x-4y-16= | | 3x+x-5=(x-2) | | x^(1/3)=5 | | 7.6=y-4.8 | | C=3.50+1.25(m-1) | | -5.09x+2.785=5.5(2.2x-.05)-7.5x | | 3x+1=-11+2x | | X^3-3x^2-4x-70=0 | | y^2(-2+-1y)(9+-1y)=0 | | 3/8+(-4/5)+(-3/8)=5/4 | | 9*2+2y=72 | | x^4+9x^3-15x^2+15=0 | | 9x+2*0=72 | | 9*0+2y=72 | | -10x-55=75 | | x^2+2x+24=12x | | (5x^2z^5-9z^3)(-8x^6z)=0 | | 2/3y=20 | | 5.6x-5.1=1.06 | | (7y^2-4y+1)(8y^2-6y)= | | [-6]= | | 4/5y+7/y-2 | | 2x-5=-55 | | -9(5)= | | 6X-19=89 | | x/-7=-21 | | -12-(-9)= | | h=-16t^2+117.5t+0 |